Subseasonal to Annual Long-Term Trends in Climate Extremes Over East Asia, 1981–2021 - Moon, Ja-Yeon; Choi, Youngeun; Kim, Yujin; Min, Sookjoo (Frontiers in Earth Science, 2022)
This study examines the up-to-date observed trends of subseasonal to annual range climate extremes over the East Asia region using the high-resolution global unified gauge-based analysis of the NOAA Climate Prediction Center for 1981–2021. The spatial extent of extreme events is identified using the Expert Team on Climate Change Detection and Indices (ETCCDI)-based modified climate extreme index (EmCEI) with five subcomponents (maximum temperature, minimum temperature. total rainfall, heavy rainfall, and wet and dry days). By combining the spatiotemporal fields into a simple index, trends in climate extremes are systematically obtained in various time ranges. Annual and semi-annual long-term trends in East Asia showed a statistically significant increase in the percentage of area affected by the upper-extreme climate (warm days, warm nights, wet extreme) and concurrently by the decrease of lower-extreme climate (cool days, cool nights, dry extreme). As the time range becomes higher, the tendency is consistent but extremeness depends on seasons and calendar months. The total EmCEI shows an increasing trend greater in the warm (summer) season than in the cold (winter) season. The temperature extreme components (C1 and C2) are dominated in spring and summer. In the subseasonal months, March has the highest trend among the calendar months both in C1 and C2. The increasing trend is consistently distinct in the 2010s for all time ranges and all components. The long-term trend in winter exhibits distinctive features of the smallest increase than in other seasons and months caused by robust interannual to multidecadal variability in the 1990s–2000s. The area affected by heavy rainfall is mainly dominated in summer while the total rainfall and wet day extreme extend in summer and fall, respectively. The EmCEI suggests that the change in the spatial extent of climate extremes is mainly caused by a shift in temperature and rainfall distributions toward warm and wet extremes over East Asia.